Tuberculosis infection control measures in healthcare facilities in Moyen-Ogooué Province, Gabon - Anja Vigenschow; Bayodé Romeo Adegbite; Jean-Ronald Edoa; Abraham Alabi; Akim A. Adegnika; Martin P. Grobusch; Marguerite Massinga-Loembe (BMC, 2021)
Abstract Background Healthcare workers (HCW) are at higher risk of tuberculosis (TB) than the general population. We assessed healthcare facilities for their TB infection control standards and priorities. Methods A standardised tool was applied. The assessment was conducted by direct observation, documents review and interviews with the facility heads. Results Twenty healthcare facilities were assessed; 17 dispensaries, an HIV-clinic, a private not-for-profit hospital and a public regional hospital. In both hospitals, outpatient departments, internal medicine wards, paediatric wards, emergency departments; and the MDR-TB unit of the public regional hospital were assessed. In Gabon, there are currently no national guidelines for TB infection control (TBIC) in healthcare settings. Consequently, none of the facilities had an infection control plan or TBIC focal point. In three departments of two facilities (2/20 facilities), TB patients and presumed TB cases were observed to be consistently provided with surgical masks. One structure reported to regularly test some of its personnel for TB. Consultation rooms were adequately ventilated in six primary care level facilities (6/17 dispensaries) and in none of the hospitals, due to the use of air conditioning. Adequate personal protective equipment was not provided regularly by the facilities and was only found to be supplied in the MDR-TB unit and one of the paediatric wards. Conclusions In Moyen-Ogooué province, implementation of TBIC in healthcare settings is generally low. Consequently, HCW are not sufficiently protected and therefore at risk for M. tuberculosis infection. There is an urgent need for national TBIC guidelines and training of health workers to safeguard implementation.